Proline isomerization modulates the bacterial IsdB/hemoglobin interaction: an atomic force spectroscopy study - Francesca Pancrazi; Omar De Bei; Francesco Lavecchia di Tocco; Marialaura Marchetti; Barbara Campanini; Salvatore Cannistraro; Stefano Bettati; Anna Rita Bizzarri (Discover Nano)
Abstract Iron surface determinant B (IsdB), a Staphylococcus aureus (SA) surface protein involved in both heme iron acquisition from host hemoglobin (Hb) and bacterial adhesion, is a proven virulence factor that can be targeted for the design of antibacterial molecules or vaccines. Recent single-molecule experiments on IsdB interaction with cell adhesion factors revealed an increase of the complex lifetime upon applying a stronger force (catch bond); this was suggested to favor host invasion under shear stress. An increased bond strength under mechanical stress was also detected by Atomic Force Spectroscopy (AFS) for the interaction between IsdB and Hb. Structural information on the underlying molecular mechanisms at the basis of this behaviour in IsdB-based complexes is missing. Here, we show that the single point mutation of Pro173 in the IsdB domain responsible for Hb binding, which weakens the IsdB:Hb interaction without hampering heme extraction, totally abolishes the previously observed behavior. Remarkably, Pro173 does not directly interact with Hb, but undergoes cis–trans isomerization upon IsdB:Hb complex formation, coupled to folding-upon binding of the corresponding protein loop. Our results suggest that these events might represent the molecular basis for the stress-dependence of bond strength observed for wild type IsdB, shedding light on the mechanisms that govern the capability of SA to infect host cells.